A geometric phasor extremum seeking control approach with measured constraints - Atta, Khalid Tourkey; Guay, Martin; Lucchese, Riccardo (Proceedings of the IEEE Conference on Decision & Control, 2019)
In this paper, we propose an extension for the phasor extremum seeking control approach to solve constrained optimization problems. The proposed technique uses phasor estimates of the objective function and the constraints to compute a geometric constraint satisfaction approach that avoids the violation of the constraints. The proposed method is illustrated to solve several nonlinear optimization problems subject to equality and inequality constraints. Finally, the effectiveness of the proposed approach is illustrated for the optimal operation of a parallel isothermal stirred-tank reactor system.